(untitled) (Journal of the College of Basic Education, 2026)
This research aims to identify the effectiveness of the focused lists strategy in improving the chemistry achievement of second intermediate grade students. The null hypothesis was formulated as follows: There is no statistically significant difference at the (0.05) level between the mean scores of the experimental group students who will study chemistry using the focused lists strategy and the mean scores of the control group students who will study using the traditional method on the achievement test. The researcher conducted an experiment that lasted for an entire semester, using a quasi-experimental approach with partial control and a post-test. The sample consisted of 72 male students from the second intermediate grade at Al-Sibtain Mixed School, affiliated with the General Directorate of Education in Babylon/Al-Mahawil. The students were divided into two groups: an experimental group and a control group. The researcher rewarded both the experimental and control groups on variables such as parental educational attainment, prior achievement in chemistry, age (calculated in months), prior knowledge tests, and Raven’s Progressive Matrices. As for the research instrument, an achievement test consisting of 40 multiple-choice items was developed. The psychometric properties were calculated, and the data were analyzed and statistically processed. The results showed a statistically significant difference (p < 0.05) between the mean scores of the experimental group, who studied chemistry using the focused lists strategy, and the mean scores of the control group, who studied the subject using the traditional method. This difference favored the experimental group.